Funnel Charts to streamline Conversions in Monitoring and Data Analytical Tools - Aakash Aluwala (North American Journal of Engineering Research, 2022)
The paper has its focus on exploring and investigating the role of funnel charts in improving and optimizing the conversion process of users within monitoring and data analytical tools. It has further been deduced that funnel charts visually show progression of users through sequential stages, giving imperative insights for assessing bottlenecks and improving the overall experience of users as well. The paper further looks into the evolution of funnel charts, the overall application across varied sectors, and discusses the strategies of implementation. The findings show how funnel charts allow data-driven decision-making, enhance conversion rates, and enable growth of business.